Reduction of aerosol and droplet dispersions using intraoral and extraoral vacuums for dental treatments with face-up, diagonal and upright positions - Tomonari Kajita; Kenji Kikuchi; Hiromitsu Morishima; Jun Watanabe; Yoko Iwamatsu-Kobayashi; Hiroyasu Kanetaka; Wataru Yashiro; Kensuke Yamauchi; Hiroshi Egusa (BMC, 2024)
Abstract Purpose The COVID-19 pandemic has affected lives and dental treatment. Aerosols and droplets generated during dental treatment present a risk of infection for dental care workers. However, detailed elucidation of the conditions under which those are generated has yet to be presented, and no clear countermeasures for protection have been established. The present study aimed to clarify the process of generation of aerosol and droplets in dental treatment, as well as their dynamics for establishment of effective countermeasures and protection strategies. Methods Images were obtained using a high-speed camera of aerosol and droplets generated during dental treatments performed on a mannequin. The effects of intraoral vacuum and extraoral vacuum to reduce those, as well as splash range with different body position were examined. Quantitative evaluations of aerosol and droplets were also performed using water-sensitive paper. Results Aerosol and droplets quantities were significantly reduced by use of both intraoral and extraoral vacuums as compared to no vacuum in both image analysis and findings obtained with water-sensitive paper (p < 0.05). Additionally, the intensity of aerosol and droplets when using the intraoral and extraoral vacuum devices with a body position of 45 degrees was a significantly less as compared to the other settings (p < 0.001). Conclusions The present study demonstrated the effectiveness of visualization of the aerosol and droplets generated by dental tools using a high-speed camera. Use of an extraoral vacuum resulted in a reduction of those generated during simulated dental treatment, and also contributed to diffusion prevention to protect the operator and assistant. Nevertheless, it is necessary to be careful because the use of extraoral vacuums may reverse the spread of aerosol and droplets depending on the position of patient.